A qualitative case study of community corrections case managers' experiences with TGNC clients - Ellis, Taylor, author; Opsal, Tara, advisor; Nowacki, Jeffrey, committee member; Jacobi, Tobi, committee member (Colorado State University. Libraries, 2022)
This thesis seeks to understand how community corrections case managers work with transgender and gender-nonconforming (TGNC) clients within the context of a facility that relies on the gender binary in its physical structure and institutional practices. Using case study and feminist methodologies, as well as semi-structured interview techniques, I interviewed 11 case managers from this facility. Participants identified as having worked with a TGNC client in the past (either directly through case management or indirectly in a managerial or security position), having worked with women in some capacity, or having received gender-responsive training. The results from this thesis present several important findings. Such findings include that because of sex-segregated housing requirements, case managers must rely on programming opportunities for their TGNC clients to receive gender-affirming care, which creates uncertainty as these opportunities vary across clientele. Additionally, while case managers disagree on the fairness of housing TGNC clients with cisgender men, they fear that housing TGNC clients with women would be dangerous; simultaneously, case managers grapple with the fear that their TGNC clients might be sexually assaulted while living on the men's side. Underlying these first two findings, case managers report a pervasive lack of institutional training to help them navigate working with this specialized population, causing them to rely on alternative knowledge sources, such as their own identities, other case managers, and clients themselves. This thesis concludes with recommendations to the facility pertaining to training and institutional practices that could be modified to better serve their TGNC clients.